Elementary evolution in coal under natural conditions: Coals affected by igneous intrusions. (15th February 2023) - Wang, Shaoqing; Chen, Hao; Wang, Xiaoling; Tang, Yuegang; Liu, Shimin; Schobert, Harold H.; Song, Xiaoxia; Zeng, Fangui
Highlights: Coal used show different elementary evolution with coal normal coalification. Three evolution pathways (Tracks I, II, and III) were explored. Track III has anomalously high the O/C atomic ratio. Coal with anomalously high O/C value at a certain distance from the intrusion. Abstract: The elementary evolution of coals affected by igneous intrusions differs from the track of coals that have undergone normal coalification. This evolution pathway is related to the natural geological conditions. To study the evolution of coals affected by igneous intrusions, a sizeable amount of data from our group and from previous works were collected and comprehensively analyzed. Based on the analyses, the H/C vs O/C evolutionary diagrams of coals affected by igneous intrusions was plotted, and three evolution pathways (Tracks I, II, and III) were found. Track I is a curve similar to the evolutionary track of coals that experienced normal coalification, as would be seen in the van Krevelen diagram. Track II is a straight line starting from H/C of about 0.8. Compared with Tracks I and II, the O/C atomic ratio is anomalously high in Track III. Track I is formed by a combination of comparatively slow dehydrogenation and fast deoxygenation; Track II is formed by a combination of comparatively faster dehydrogenation and slower deoxygenation; and Track III is formed by a process resulting in increased oxygen content, and regardless of dehydrogenation. Carbonate minerals played an important role in the anomalously high O/C atomic ratio in Track III. However, carbonate minerals were affected by temperature, and a high temperature can form pyrolytic carbon in coals affected by intrusions and reduce carbonate minerals content by consuming carbon dioxide. Coals with anomalously high O/C values are not coals that were in direct contact with intrusions but are found at a certain distance from the intrusions.